Orthodontic considerations of functional occlusion in Class Ð† normal occlusion - Al-Nassar, Doaa B; Al-Hashimi, Hadeel A (Journal of Baghdad College of Dentistry, 2015)
Background: The therapeutic goal of orthodontic treatment is to establish ideal occlusion which includes both static and functional aspects. The objective of this study was to clarify functional occlusal treatment goals by analyzing functional occlusion in subjects with established normal occlusion and identify the differences between canine protected occlusion and group function occlusion. Materials and Methods: The sample consisted of 62 subjects with normal occlusion and with an age range of (18-25 years).Functional occlusal contacts during lateral excursion were identified on a fully adjustable articulator, and then the samples were classified according to: 1) Type of functional occlusion: A) Canine protected occlusion group (canine protected occlusion on both working sides). B) Group function occlusion group (group function occlusion on both working sides). C) Mixed functional occlusion group (canine protected occlusion on one side and group function occlusion on the other side (. 2) Working side contact into: Canine protected occlusion (62 sides) and group function occlusion (62 sides). Then different variables were analyzed. Results: Results revealed that vertical canine overlap, position of maxillary canine and 1st molar mesiobuccal cusp tip to the center of opposing embrasure/groove, and arch form analysis had significant difference between groups. Adding to that, some of the maxillary and mandibular teeth were significantly differed between groups in regard to crown angulation and inclination. Conclusions: It was concluded that the vertical canine overlap, position of maxillary canine and 1st molar mesiobuccal cusp tip to the center of the opposing embrasure/groove, arch form harmony were important functional aspects of orthodontic treatment goals.